2021
DOI: 10.1002/er.7089
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid TSA‐RBFNN based approach for MPPT of the solar PV panel under the effects of tilt angles variations and environmental effects

Abstract: This paper proposes a hybrid approach to improve the performance of photovoltaic (PV) system and track the maximum system power. The proposed hybrid approach is the combination of Tunicate Swarm algorithm (TSA) and Radial Basis Function Neural Network (RBFNN), hence it is called TSA-RBFNN. The main contribution of this paper is to "achieve the best output from solar system by tilt angles variations and environmental effects, like dust accumulation, water drops, partial shading, and maximum power point tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The module/array undergoes a faster and more dynamic solar insolation shift during cloudy days, which has a direct impact on its performance [ 37 ]. Under PSCs, unshaded modules receive a certain amount of solar irradiation, while shaded modules receive less than that amount [ 38 ]. This imbalance in irradiance causes a hotspot in the module that receives less irradiance [ 39 ].…”
Section: Effect Of Psc On Pv Systemmentioning
confidence: 99%
“…The module/array undergoes a faster and more dynamic solar insolation shift during cloudy days, which has a direct impact on its performance [ 37 ]. Under PSCs, unshaded modules receive a certain amount of solar irradiation, while shaded modules receive less than that amount [ 38 ]. This imbalance in irradiance causes a hotspot in the module that receives less irradiance [ 39 ].…”
Section: Effect Of Psc On Pv Systemmentioning
confidence: 99%
“…Considering extreme load growth, Kommula and Kota (2022) focused primarily on proposing a new method of TSA to optimize the integration of electrical distribution networks. Ganti et al (2021) improved TSA to control the speed and torque errors of brushless DC motors. Gharehchopogh (2022) used TSA to optimize the radial basis function neural network to improve maximum system power tracking in a photovoltaic system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study will use this value as an input for the model during the simulation. Meanwhile, hourly extraterrestrial irradiance on the horizontal surface I 0 can be calculated through Equation (8) In this equation, G sc is the solar constant, which is 1367 W/m 2 , with up to 1% error. φ is the latitude and is related to the simulation location, and ω is the hour angle, the output of the solar position model.…”
Section: Liu-jordan Modelmentioning
confidence: 99%
“…Recent studies have shown that tilt angle optimization can significantly increase the solar irradiance incident on panels, which subsequently provides greater solar to electricity conversion [6][7][8]. Raina et al [6] found that a bifacial photovoltaic module installed at an optimum orientation could collect up to 84.76% more irradiance.…”
Section: Introductionmentioning
confidence: 99%